地域日本語教育・支援に関わる人に 求められる資質・能力 - 郎, 横溝紳一 (VNU Journal of Foreign Studies; Vol 28 No 4, 2012)
Abstract. This article attempts to clarify the necessities for people who are involved in teaching/supporting Japanese as a second language in local areas.  By utilizing the analysis approach of ‘a good language teacher’, it became clear that Ms. Yuko Kitagawa, a good educator/supporter example, fulfills all of the characteristics of a good educator/supporter suggested by Shimada (2011), and that she has a strong kakugo (preparedness) to assist people from foreign countries.